Interleukin-18 in metabolism: From mice physiology to human diseases - Somm, Emmanuel; Jornayvaz, François R. (Frontiers in Endocrinology, 2022)
Interleukin-18 (IL-18) is a classical member of the IL-1 superfamily of cytokines. As IL-1β, IL-18 precursor is processed by inflammasome/caspase-1 into a mature and biologically active form. IL-18 binds to its specific receptor composed of two chains (IL-18Rα and IL-18Rβ) to trigger a similar intracellular signaling pathway as IL-1, ultimately leading to activation of NF-kB and inflammatory processes. Independently of this IL-1-like signaling, IL-18 also specifically induces IFN-γ production, driving the Th1 immune response. In circulation, IL-18 binds to the IL-18 binding protein (IL-18BP) with high affinity, letting only a small fraction of free IL-18 able to trigger receptor-mediated signaling. In contrast to other IL-1 family members, IL-18 is produced constitutively by different cell types, suggesting implications in normal physiology. If the roles of IL-18 in inflammatory processes and infectious diseases are well described, recent experimental studies in mice have investigated the action of IL-18 signaling in the control of energy homeostasis, pancreatic islet immunity and liver integrity during nutritional stress. At the same time, clinical observations implicate IL-18 in various metabolic diseases including obesity, type 1 and 2 diabetes and nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH). In the present review, we summarize and discuss the physiological actions of IL-18 in metabolism and its potential roles in pathophysiological mechanisms leading to the most common human metabolic disorders, such as obesity, diabetes and NAFLD/NASH.